2012
DOI: 10.1159/000341574
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Spectral-Domain Optical Coherence Tomography and Heidelberg Retina Tomograph III Optic Nerve Head Parameters in Glaucoma

Abstract: Background: To evaluate the agreement between the optic nerve head (ONH) measurements obtained by spectral-domain optical coherence tomography/scanning laser ophthalmoscope (SD-OCT/SLO) and the Heidelberg retinal tomograph III (HRT-III), and to compare the ONH measurements of both devices in different glaucoma types. Methods: In a prospective study, 30 patients with primary open-angle glaucoma (POAG) and 30 patients with pseudoexfoliation glaucoma (PXG) were enrolled. All patients underwent SD-OCT/SLO and HRT-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 36 publications
3
11
0
1
Order By: Relevance
“…13 Hence, cup measurements are higher by RTVue-100 than HRT3, and rim measurements are higher by HRT3 than RTVue-100. 14 Tan et al 15 already demonstrated that HRT rim area has the highest variability due to reference plane position. In fact, rim area is measured where the reference plane intersects the ONH on the z-axis, so any z-axis shifts between the ONH and the reference plane due to variation in ONH and peripapillary topography, reference plane or both, could affect rim area measurements.…”
Section: Discussionmentioning
confidence: 99%
“…13 Hence, cup measurements are higher by RTVue-100 than HRT3, and rim measurements are higher by HRT3 than RTVue-100. 14 Tan et al 15 already demonstrated that HRT rim area has the highest variability due to reference plane position. In fact, rim area is measured where the reference plane intersects the ONH on the z-axis, so any z-axis shifts between the ONH and the reference plane due to variation in ONH and peripapillary topography, reference plane or both, could affect rim area measurements.…”
Section: Discussionmentioning
confidence: 99%
“…4,5,7 A new generation of SD-OCT devices provide highquality images of retinal layers and allow quantitative assessment of RNFL and ONH. 12,13 Although SD-OCT is an effective technology for supplying structural data, clinicians hope to verify structural damage with corresponding functional changes. Standard automated perimetry is the main method for detecting functional glaucomatous damage, whereas it was suggested that clinically relevant VF defect usually manifests many years after initial structural damage.…”
Section: Discussionmentioning
confidence: 99%
“…Taking advantage of the principle of confocal microscopy, confocal SLO moves a confocal aperture between two end points to obtain a number of tomographic slices and to extract depth information [21,22] . Confocal SLO and OCT have become standard instruments for scanning the optic nerve head in glaucoma and are widely being used for imaging the RNFL [23,24] . Another important feature of SLO is the use of different wavelength lasers to enable a pseudocolor fundus image.…”
Section: Scanning Laser Ophthalmoscope (Slo) and Adaptive Optics (Ao)mentioning
confidence: 99%
“…The Optos captures an appreciably wider view of the retina temporally and nasally, despite of peripheral distortion, while the ultra-wide field Heidelberg Spectralis is able to image the superior and inferior retinal vasculature more peripherally [53] . Of note, the Heidelberg Spectralis provides a higher resolution image than that of Optos [23] . Recent advances in UWF imaging software, such as stereographic projection software, now have been available in commercial UWF devices.…”
Section: Ultra-widefield Imagingmentioning
confidence: 99%